Management of Loading and Unloading Activities on Ships In Increasing Non-Tax State Revenue (Study at the Harbormaster’s Office and Manado Port Authority) - Piri, Marsely; Kandouw, Selpius R.; Wawointana, Thelma (Technium Social Sciences Journal, 2023)
The aim of this research is to analyze and interpret the planning, implementation, and supervision of Loading and Unloading Activities at the Port at the Port Harbormaster’s Office and Manado Port Authority in increasing Non-Tax State Revenue (PNBP). The focus of the researcher’s problem on the phenomenon that occurs is how to plan, implement, and supervise loading and unloading activities on ships so that it can increase non-tax state revenue at the Harbormaster’s Office and the Manado Port Authority. The method used in this research is a qualitative approach. The results of the research show that the Harbormaster’s Office and the Manado Port Authority in managing loading and unloading activities on ships to increase non-tax State Revenues have not run optimally so the PNBP targets at the Harbormaster’s Office and the Manado Port Authority are not met.